Thrombotic sinusoiditis and local diffuse intrasinusoidal coagulation in the liver of subjects affected by COVID-19: the evidence from histology and scanning electron microscopy - Fanni, D; Cerrone, G; Saba, L; Demontis, R; Congiu, T; Piras, M; Gerosa, C; Suri, J S; Coni, P; Caddori, A; Piga, M; Mancosu, G; et al. (European review for medical and pharmacological sciences, 2021)
Liver injury has been reported in patients with COVID-19. This condition is characterized by severe outcome and could be related with the ability of SARS-CoV-2 to activate cytotoxic T cells. The purpose of this study is to show the histological and scanning electron microscopy features of liver involvement in COVID-19 to characterize the liver changes caused by the activation of multiple molecular pathways following this infection. Liver biopsies from 4 patients (3 post-mortems and 1 in vivo) with COVID-19 were analyzed with histology and by scanning electron microscopy. The liver changes showed significant heterogeneity. The first case showed ground glass hepatocytes and scattered fibrin aggregates in the sinusoidal lumen. The second evidenced intra-sinusoidal thrombi. The third was characterized by sinusoidal dilatation, atrophy of hepatocytes, Disse's spaces dilatation and intra-sinusoidal aggregates of fibrin and red blood cells. The fourth case exhibited diffuse fibrin aggregates in the dilated Disse spaces and microthrombi in the sinusoidal lumen. In COVID-19-related liver injury, a large spectrum of pathological changes was observed. The most peculiar features were very mild inflammation, intra-sinusoidal changes, including sinusoidal dilatation, thrombotic sinusoiditis and diffuse intra-sinusoidal fibrin deposition. These findings suggested that a thrombotic sinusoiditis followed by a local diffuse intra-vascular (intra-sinusoidal) coagulation could be the typical features of the SARS-CoV-2-related liver injury.